Coral-based reconstruction of interannual and decadal SST variability in the northern South China Sea during the mid-Holocene - Zhiheng Wu; Tingli Yan; Rui Tang; Ben Wang; Yanjun Mei; Ning Zhao (Geo-Marine Letters, 2026)

Rap1b is a critical regulator of germinal vesicle breakdown in porcine oocytes - Mingyue Sui; Zhihao Wang; Jianqiang Sun; Ruohan Mei; Mingju Sun; Yichen Liu; Xiang Gao; Youwei Li; Yanjun Huan (Theriogenology, 2026)

Holocene climate optimum moisture variability in the monsoon marginal zone of northern China revealed by multi-proxy stalagmite records - Shouyi Huang; Yanjun Cai; Gang Xue; Xinhui Zhang; Mei He; Ruoxin Li; Yingying Wei; Le Ma; Xing Cheng; Haiwei Zhang; Hai Cheng (Global and Planetary Change, 2026)

The Holocene stalagmite trace element and Sr isotope records from Central China and the inferred hydroclimate changes - Yuting Wu; Yanjun Cai; Fugui Xiao; Mei He; Shouyi Huang; Xiangkun Zhai; Ruoxin Li; Gang Xue; Hanying Li; Chunlei Zong; Hai Cheng (Chemical Geology, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

Short-term emissions effect of rainfall erosion on soil CO2 in red soil sloped farmland in southern China - Keyu Yan; Xiaohan Mei; Chuan Zhang; Yanmei Hu; Daoxiang Wang; Zhengfa Chen; Xiaofeng Yang; Yanrui Shao; Yanjun Mao (Soil and Tillage Research, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

Different responses of soil bacterial necromass carbon and fungal necromass carbon to nitrogen deposition in meadow steppe - Na Jiang; Hao Zhang; Siyu Zhang; Jie Qin; Hui Wang; Yanjun Zhang; Dianlin Yang; Lili Wang; Qiannan Yang; He Ye; Mei Hong; Haifang Zhang (Applied Soil Ecology, 2025)

Annually laminated stalagmite inferred variations of precipitation and temperature in northern China over the last 150 years - Yingying Wei; Yanjun Cai; Xing Cheng; Gang Xue; Kang’en Zhou; Le Ma; Yanbin Lu; Shouyi Huang; Mei He; Hai Cheng; R. Lawrence Edwards (Climate Dynamics, 2025)

Rational design of hierarchical porous structure of ZSM-22 for boosting high-efficiency selective hydrogenation of oleic acid to jet fuel - Zhentao Liu; Jinlin Mei; Xiaoyang Kong; Zikang Chen; Dong Li; Haidong Li; Chunya Wang; Yanjun Gong; Chunming Xu; Xilong Wang (Chemical Engineering Journal, 2025)

Mechanochromic luminescent material with high quantum yield for multi-mode anti-counterfeiting applications - Yongxian Guo; Aoli Wu; Qiaoru Zhang; Mei Zhao; Yanjun Gong; Shuya Liu; Mashooq Khan; Haoyang Song; Juyoung Yoon; Qiongzheng Hu (Chemical Engineering Journal, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Ultrafine Pt particles on hollow hierarchical porous β zeolites for selective hydrogenation of naphthalene - Zhentao Liu; Jinlin Mei; Dandan Wang; Xiaoyang Kong; Ke Yu; Zhengkai Cao; Chunya Wang; Yanjun Gong; Aijun Duan; Chunming Xu; Xilong Wang (Fuel, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

Hierarchical porous Pt/Hβ catalyst with controllable acidity for efficient hydrogenation of naphthalene - Zhentao Liu; Enhua Wang; Jinlin Mei; Aocheng Wang; Yutong Zou; Chunya Wang; Hui Shang; Yanjun Gong; Aijun Duan; Chunming Xu; Xilong Wang (Chemical Engineering Journal, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Highly sensitively detection of amine vapors released during shrimp spoilage by fluorescent molecules locked in covalent organic frameworks - Jingru Mi; Yongxian Guo; Yanjun Gong; Shuya Liu; Mei Zhao; Qiongzheng Hu; Li Yu (Food Chemistry, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Recent trends in degradation strategies of PFOA/PFOS substitutes - Zizi Li; Zhi-Mei Luo; Yanjun Huang; Jia-Wei Wang; Gangfeng Ouyang (Chemosphere, 2023)

Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China - Xiaoyu Tian; Xiaobing Shan; Li Ma; Chenyang Zhang; Mei Wang; Jie Zheng; Ruoyi Lei; Li He; Jun Yan; Xun Li; Yanjun Bai; Keqin Hu; et al. (Environmental Pollution, 2023)

Optimization of medical waste recycling network considering disposal capacity bottlenecks under a novel coronavirus pneumonia outbreak - Xueyun Mei; Hao Hao; Yichen Sun; Xinyang Wang; Yanjun Zhou (Environmental Science and Pollution Research, 2022)

Effectiveness of predicting spatial contaminant distributions at industrial sites using partitioned interpolation method - Pengwei Qiao; Sucai Yang; Wenxia Wei; Peizhong Li; Yanjun Cheng; Shuang Liang; Mei Lei; Tongbin Chen (Environmental Geochemistry and Health, 2021)

Spatial Pattern of Female Non-agricultural Employment and Its Driving Forces in Guangdong Province, China: A Perspective of Individual and Family-level - Zhanhui Fu; Lin Mei; Yanjun Liu; Junfeng Tian; Rumin Zheng; Jing Tian (Chinese Geographical Science, 2020)

Comparison of common spatial interpolation methods for analyzing pollutant spatial distributions at contaminated sites - Pengwei Qiao; Peizhong Li; Yanjun Cheng; Wenxia Wei; Sucai Yang; Mei Lei; Tongbin Chen (Environmental Geochemistry and Health, 2019)

Calreticulin protects the HT22 hippocampal neurons from injury induced by hypoxia - Zhaoping Wang; Mei Yang; Jian Xue; Yanjun Chong (Molecular & Cellular Toxicology, 2018)